EKSPRESI p53 DAN p16 PADA LOW GRADE DAN HIGH GRADE SEROUS CARCINOMA OF OVARII - Yuliawaty - (Oceana Biomedicina Journal, 2023)
Background Ovarian serous carcinoma is a common ovarian epithelial malignancy, divided into low grade serous carcinoma (LGSC) and high grade serous carcinoma (HGSC). HGSC accounts for 60-80% of ovarian carcinomas and is the most aggressive type and has a poor prognosis. The literature has described various genetic mutations involved in the occurrence of HGSC, one of which is p53 and p16 mutations. Diagnostic and prognostic value of LGSC and HGSC related to its targeted therapy.Objective This study aimed to analyze the differences in the expression of p53 and p16 in LGSC and HGSC at anatomical pathology of laboratory dr. Kariadi Hospital.Methods : This study was an observational analytic study with a cross sectional design involving 65 patients with ovarian serous carcinoma diagnosed between January 2017 and December 2021. The data collected were age, LGSC and HGSC subtypes as well as p53 and p16 expressions were obseved by a pathologists and a resident. Compatibility between observers were tested using Kappa test. Data analysis used Chi square test and Fisher's exact test. Results This study included 65 patients aged between 30-68 years, consist of 50 patients with HGSC and 15 patients with LGSC (P <0,001). Kappa test results between two observers showed a score of k = 0,88. Conclusion There is a significant difference between the expression of p53 and p16 in HGSC, as the expression of p53 and p16 is much stronger and diffuse in high grade serous carcinoma compared to LGSC.